2022
DOI: 10.3390/ijerph19063235
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Rural Food Security in High Income Countries: A Systematic Literature Review

Abstract: Prior to the COVID-19 pandemic, rural-dwelling people in high-income countries were known to have greater challenges accessing healthy food than their urban counterparts. The COVID-19 pandemic has impacted food supplies across the world, and public health restrictions have changed the way people shop for food, potentially exacerbating food insecurity. This systematic literature review aimed to synthesize the available evidence on the impact of the COVID-19 pandemic on aspects of food insecurity in rural popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 61 publications
3
21
1
Order By: Relevance
“…Interestingly, in our study, rurality was significantly associated with food insecurity at Surveys 1 and 2, but not 3, which may relate to the fact that challenges with food security in rural areas are compounded by lower availability and access to healthy food when the food supply is disrupted. These results align with recent review of food insecurity in rural regions of high income countries during the COVID-19 pandemic [44] that demonstrated that food insecurity was often significantly higher in rural regions, which was often related to lower food availability and access to food during the pandemic. Given the stability of the food supply had recovered by May 2021, this could indicate that temporary food supply challenges disproportionately affected rural-dwelling Australians, extending previously published research [4].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, in our study, rurality was significantly associated with food insecurity at Surveys 1 and 2, but not 3, which may relate to the fact that challenges with food security in rural areas are compounded by lower availability and access to healthy food when the food supply is disrupted. These results align with recent review of food insecurity in rural regions of high income countries during the COVID-19 pandemic [44] that demonstrated that food insecurity was often significantly higher in rural regions, which was often related to lower food availability and access to food during the pandemic. Given the stability of the food supply had recovered by May 2021, this could indicate that temporary food supply challenges disproportionately affected rural-dwelling Australians, extending previously published research [4].…”
Section: Discussionsupporting
confidence: 90%
“…Due to COVID-19, 3.3 billion global workforces are at risk of losing their livelihood [ 14 ]. The food insecurity due to COVID-19 affects the global society regardless of their economic status [ 15 , 16 ], but the severity of the food insecurity is substantial in lower income countries than developed one [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, trends on social media and online cooking classes seem to support this result (Ghosh et al, 2020;Grabia et al, 2020;Amataiti et al, 2021;Carvalhal et al, 2021;Kishimoto et al, 2021). In the study of Kent et al (2022), these changes in eating habits were also reported in the normal population during the COVID-19 lockdown and social distancing (Kent et al, 2022). Even though most patients tended to consume more fresh fruits, vegetables, and grains, this inclination faced difficulties such as limited access and availability of fresh food and disruptions in food distribution (Ghosh et al, 2020;Grabia et al, 2020;Olickal et al, 2020;Ruiz-Roso et al, 2020;Sankar et al, 2020;Amataiti et al, 2021;Carvalhal et al, 2021;Kishimoto et al, 2021;Vetrani et al, 2021;Maruo et al, 2022).…”
Section: Discussionmentioning
confidence: 78%